Detection of Bovine Respiratory Syncytial Virus in Cattle: A Systematic Review and Meta-Analysis - Gebremeskel Mamu Werid; Ashenafi Kiros Wubshet; Teshale Teklue Araya; Darren Miller; Farhid Hemmatzadeh; Michael P. Reichel; Kiro Petrovski (Ruminants)
Bovine respiratory syncytial virus (BRSV) is an economically important pathogen of cattle and contributes to the bovine respiratory disease complex (BRDC). Despite individual studies investigating BRSV prevalence, risk factors, and detection methodologies, a systematic review and meta-analysis have been lacking. The aim of the current study was to conduct a systematic review and meta-analysis to determine the prevalence and detection rate of BRSV and identify associated risk factors. Additionally, the study aimed to explore the variability in BRSV prevalence based on different detection methods and associated risk factors. Adhering to PRISMA guidelines, data from three databases—Web of Science, PubMed, and Scopus—were systematically retrieved, screened and extracted. Out of 2790 initial studies, 110 met the inclusion criteria. The study found that prevalence and detection rates varied based on the detection methods used (antibody, antigen, and nucleic acid), study populations, production systems, and geographic locations. Findings were reported as a pooled proportion. The pooled proportion, hereafter referred to as prevalence or detection rate, was determined by calculating the ratio of cattle that tested positive for BRSV to the total number of cattle tested. Key findings include a pooled prevalence of 0.62 for antibody-based methods, 0.05 for antigen-based methods, and 0.09 (adjusted to 0.03) for nucleic acid-based methods. Detection rates in BRDC cases also varied, with antibody methods showing a rate of 0.34, antigen methods 0.16, and nucleic acid methods 0.13. The certainty of evidence of the meta-analysis results, assessed using GRADE, was moderate for antibody detection methods and low for antigen and nucleic acid methods. The study identified significant risk factors and trends affecting BRSV prevalence, such as geographical location, herd size, age, and co-infections. The results of the current study showed the complexity of understanding BRSV prevalence in different settings. The variability in BRSV prevalence based on detection methods and associated risk factors, such as geographic location and herd size, highlights the need for tailored approaches to detect and manage BRSV accurately.